Pemanfaatan Google Sheets dan Google Form untuk Layanan Administrasi Mahasiswa Menggunakan Konsep Electronic Service Quality - Asqia, Misna; Nabarian , Tifanny (Jurnal Teknologi Terpadu, 2021)
The COVID-19 pandemic has impacted higher education activities, including the student administration service process at the Nurul Fikri STT Terpadu BAAK. The problem faced is that the process of submitting letter requirements is still manual. As a result of this manual submission, students who need letters cannot come face-to-face to campus. Of course, this will impact BAAK's performance in serving the administrative needs of students. Because of this, this article then provides a solution in the form of using Google Sheets and Google Forms for the student administration submission process. Google Sheets and Google Forms are choices because they are cloud-based storage systems and can use by anyone without being limited by place and time. This study used electronic Service Quality (E-SQ) and User Acceptance Test (UAT) as the test and questionnaires as a data collection tool. The dimensions used in E-SQ are efficiency, fulfillment, and system availability. The study results obtained two categories, namely the results of processing student data and BAAK staff data. The percentage of student results is as follows. The efficiency dimension is 86%. Fulfillment is 82.5%, and the system available is 82.5%. The percentage of results of BAAK staff is as follows. Efficiency is 86.67%, fulfillment is 90%, and the system available is 100%.